Measuring corporate governance performance beyond the financial metrics: A study based on deposit money banks in Nigeria (2019)
Studies on corporate governance and firm performance have traditionally used financial metrics such as return on investment, return on assets, return on equity, profitable after tax, earnings per share, firm value (Tobin's q), and other quantifiable matrices. These performance measurement indicators, however, do not fully account for the social and environmental benefits derivable from corporate activities. This study differed from this approach by measuring corporate performance of deposit money banks in Nigeria using the sustainability reporting and triple bottom line (TBL) framework. Two TBL‐compliance metrics were developed that tracks the performanceof banks along the TBL parameters, which is more robust than the usual financial indicators. Six banks were selected for the study and were assigned scores based on their relative achievement in the adoption process of 17 identified metrics in the TBL framework. The results showed that Nigerian banks lacked behind in corporate governance performance based onTBL framework. On the aggregate, the level of spending on corporate social activities as a percentage of profit after tax was less than 1% for the 10‐year period reviewed (2013–2017). The study showed that all the sampled banks had put in place policy framework that is in tandem with the TBL template,but there is still a mix match between the policy enunciation and concrete investments needed to be fully TBL complaint. The study recommended that Nigerian banks should devote more resources towards meeting the increasing social, environmental,and ecological demands on them in line with global best practices.